Assessment of Paracetamol Dosing Accuracy among Caregivers in Under-5 Children (Community Based Medical Journal, 2026)
Paracetamol is one of the most commonly used antipyretics and analgesics for febrile children worldwide. Inaccurate dosing by caregivers, particularly for under-5 children who require weight-based calculation, poses a significant risk of toxicity or therapeutic failure. A prospective, cross-sectional study was conducted at the Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, from January to December of 2023, to assess the accuracy of paracetamol dosing by caregivers for their under-5 children. A total of 113 caregivers administering liquid paracetamol to their under-5 children were enrolled in this study. Data was collected through structured interviews and direct observation of the dosing process using the caregivers' own measuring devices. Dosing accuracy was determined by comparing the intended dose with the weight-based recommended dose (15 mg/kg). Among those 113 caregivers, the prevalence of dosing inaccuracy was 68.1%, with under-dosing (52.2%) being more common than over-dosing (15.9%). Dosing accuracy was significantly associated with the measuring device used (p